PENERAPAN METODE PEMBELAJARAN ROLE PLAY UNTUK MENINGKATKAN KEAKTIFAN PESERTA DIDIK PADA MATA PELAJARAN MATEMATIKA SISWA KELAS IV SDN MELAYU MUHAMMADIYAH - Herdayanti; Nurul Qamariyah; Ernawati; Kasmila (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The problem in this research is based on the reality in class IV A of SDN Melayu Muhammadiyah is the low learning activity of students in mathematics lesson content. The problem formulation in this research is how to apply the role play learning method to increase the learning activity of students with mathematics content in class IV A at SDN Melayu Muhammadiyah. This research aims to describe the application of the role play method in increasing students' active learning. The focus of this research is the application of role play learning methods and active learning of students on mathematical content. The approach in this research is a qualitative approach with the type of classroom action research (PTK) which consists of 2 cycles which include planning, implementation, observation and reflection. The results of this research show that there is an increase in the quality of learning both in teacher learning activities and student learning activities as well as student learning activity. The results of observations of teacher teaching activities and student activities in cycle 1, meeting 1, were still in the sufficient category and at meeting 2 were in the good category, while in cycle 2 there was an increase in the good category.